Habilidades blandas y desempeño docente del nivel primario y secundario institución educativa pública Mariscal Oscar Raymundo Benavides, Iquitos 2023 - Melendez Rengifo, Joel (2025)
The purpose of the research carried out at the Mariscal Oscar Raymundo Benavides public educational institution in Iquitos in 2023 was to analyze the relationship between soft skills and teaching performance. 136 primary and secondary school teachers participated, selected through stratified random sampling. A survey was applied to measure the relevant variables. It was discovered that 19.1% of the teachers demonstrated a high mastery of soft skills, 66.2% an intermediate level and 14.7% a low level. Regarding teaching performance, 19.1% achieved high performance, 50% achieved moderate performance and 13.2% achieved low performance. The inferential analysis showed a significant and positive correlation between soft skills, particularly self-esteem, and teaching effectiveness (rs = 0.591, p<0.05). A strong connection was also observed between empathy and teaching performance (rs = 0.758, p<0.05), as well as between communication skills and teaching performance (rs = 0.639, p<0.05). These results confirmed the specific hypotheses of the study. In conclusion, a significant positive correlation was confirmed between soft skills as a whole and teaching performance (rs = 0.756, p<0.05), validating the general hypothesis of the study.